ANALISIS PENGEMBANGAN SUMBER DAYA MANUSIA, MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA UKM BUDI DAYA KELOMPOK IKAN MINA LESTARI DESA MARGA SAKTI KECAMATAN PADANG JAYA - Sulfitriah, Sulfitriah; Arini, Eti (JURNAL MANAJEMEN MODAL INSANI DAN BISNIS (JMMIB), 2021)
The purpose of this study was to determine the Analysis of Human Resource Development, Motivation and Work Discipline on Employee Performance in Mina Lestari Fish Group, Margasakti Village, Padang Jaya District. This type of research is an associative quantitative research with the work unit under study is all SME employees. The number of respondents in this study was 60 people. questionnaire data collection method. By using the analysis technique using the Regression Analysis Test using the Multiple Linear Regression Analysis Test, and Hypothesis Test, namely the t test and f test. Based on the results of this study, it shows that the development of motivational human resources and in civil servants has a positive and significant effect on employee performance. This will increase the smoothness of work and increase employee performance that is more optimal.Â Key words: Human Resources Development, Motivation and in Work Practice on employee performance.